Peran Pemuda Muhammadiyah Dalam Membangun Moderasi Beragama - Ari Farizal Rasyid; Anwar Taufik Rakhmat (Khazanah Multidisiplin, 2023)
Muhammadiyah youth generation is a communication platform for Muhammadiyah's younger generation, which contributes as a pioneer and implementer while somehow enhancing of Muhammadiyah. Because they will be the future leaders, the younger generation is crucial towards the growth of the Indonesian nation as a multicultural nation. As a reason, study on this perspective of moderation is important. This research uses a qualitative method with a sociological approach to the theory published in 2019 by the Directorate General of Education, Ministry of Religion of the Indonesian Republic as a measuring instrument in understanding religious moderation. This study attempts to present an overview of Muhammadiyah youth in Tasikmalaya Regency's understanding and attitudes on implementing Islamic moderation values in organizational and individual behavior. According to the research that has been carried out, it can be concluded that the role of youth in building religious moderation is very important. This research is expected to be able to contribute to the development of the theory of 9 values of religious moderation that is beneficial to society.